Endothelial to Mesenchymal Transition: An Insight in Atherosclerosis - Huang, Qingyan; Gan, Yuhong; Yu, Zhikang; Wu, Heming; Zhong, Zhixiong (Frontiers in Cardiovascular Medicine, 2021)
Atherosclerosis is a fundamental disease of the cardiovascular system that leads to high morbidity and mortality worldwide. The endothelium is the first protective barrier in atherosclerosis. Endothelial cells have the potential to be transformed into mesenchymal cells, in a process termed endothelial to mesenchymal transition (EndMT). On the one hand, EndMT is known to contribute to atherosclerosis by inducing a number of phenotypes ranging from endothelial cell dysfunction to plaque formation. On the other hand, risk factors for atherosclerosis can lead to EndMT. A substantial body of evidence has suggested that EndMT induces the development of atherosclerosis; therefore, a deeper understanding of the molecular mechanisms underlying EndMT in atherosclerosis might provide insights to reverse this condition.